Answer:
10=y/11-13
We move all terms to the left:
-10-(y/11-13)=0
-y/11+13-10=0
We multiply all the terms by the denominator
-y+13*11-10*11=0
We add all the numbers together, and all the variables
-1y+33=0
We move all terms containing y to the left, all other terms to the right
-y=-33
y=-33/-1
y=+33
The answer
there is no more explanation about this question, the solution can be found easily by applying the rule of transformation of rotation
for example, the properties of rotation transformation are:
A rotation preserves length but does not necessarily preserveslope of a line.
A 90° rotation ( 1/4 turn) anticlockwise about the origin changesthe point (x; y) to (-y; x).
A 180° rotation ( 1/2 turn) clockwise or anticlockwise about theorigin changes the point (x; y) to (-x;-y).
A 270° rotation ( 3/4 turn) anticlockwise changes about the originthe point (x; y) to (y;-x).
so the answer is
<span>R0, 270°</span>
Answer:1) commutative property of addition
Step-by-step explanation:
2(4x-3)-7(x+1) first distribute
8x-6-7x+7 then combine the x's
<u>x+13 </u>
Answer:
Where is the shape?
Step-by-step explanation: